The effect of date fruit consumption on early postpartum hemorrhage: a randomized clinical trial - Maryam Niknami; Maryam Farash; Mona Rahnavardi; Saman Maroufizadeh; Roya Faraji Darkhaneh (BMC, 2023)
Abstract Background Postpartum hemorrhage, anemia, and iron deficiency are important health problems. Using safe, cheap, and available methods to reduce the amount of hemorrhage after childbirth can be effective for the mother's health during this period. Therefore, this study was conducted to determine the effect of date fruit consumption on the amount of hemorrhage after natural childbirth. Methods This randomized clinical trial was conducted on 98 women referred to the maternity ward of Al-Zahra Hospital in Rasht using the available sampling method. The primary outcome was postpartum hemorrhage, measured using the Pictorial Blood Loss Assessment Chart (PBLAC). Two hours after delivery, 100 g of date fruits were given to the intervention group, and the amount of hemorrhage was recorded during the first 24 h. Comparison between the two groups was done with the Mann-Whitney test with the Hodges-Lehmann estimator and corresponding exact conditional nonparametric confidence interval (CI) as effect estimate. A P < 0.05 was considered significant. Results The median of postpartum hemorrhage after normal delivery in the date and control groups was 35.0 [interquartile range (IQR): 22.0 to 39.8] and 39.0 [IQR: 27.5 to 64.5], respectively. Using the Hodges-Lehmann estimator, on average, the median postpartum hemorrhage in the date group was 9.0 (95% CI: 2.00-18.0) units lower than the control group (P = 0.009). Conclusion Consumption of dates effectively reduces the amount of hemorrhage after natural childbirth; thus, consuming this fruit during postpartum period is recommended. Also to confirm the findings, it is recommended to conduct similar studies in this field. Trial registration This trial was registered with the Iranian Registry of Clinical Trials; https://www.irct.ir/trial/59197 (IRCT20210607051505N2) on 31/10/2021.